Framing Analysis and Student Perceptions of Israeli Product Boycott Content on Instagram (A Qualitative Descriptive Study of Communication Science Students) - Claudia, Baby Ayu; Tamsil, Ilma Saakinah (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to analyze the framing and perceptions of Communication Science students regarding content on Instagram boycotting Israeli products. The research method used a qualitative descriptive approach with data collection techniques through in-depth interviews, account observation, and upload documentation, with informants selected purposively. Data analysis refers to the Miles & Huberman model and Entman's framing theory. The results show that Instagram framing constructs a narrative of solidarity and humanitarian values ??that encourage support for the boycott. However, message reception is influenced by media literacy and personal filters, resulting in varied student perceptions. In general, students demonstrated critical awareness of the boycott issue despite varying levels of media literacy.